An Application of “Organization Development Tools” in Identifying Chinese University Students’ Learning Styles of English Language: A Case Study of Comprehensive English Subject at the College of Oriental Languages, Zhejiang Yuexiu University of Foreign Languages, People’s Republic of China - Tu, Haihua (ABAC ODI JOURNAL Vision. Action. Outcome, 2019)
The purpose of this research is to improve Chinese university students’ performance in four aspects, namely sense of responsibility, academics in students’ grades, engagement and self-esteem by using student-centered learning approach at the College of Oriental Languages (COL), Zhejiang Yuexiu University of Foreign Languages (ZYUFL). Changing students’ learning styles should be implemented with careful consideration. With that in mind, a new learning process and teaching model were designed in order to improve the teaching and learning quality. Two different groups were investigated, namely the experimental and control group. Research strategies such as open-ended and structured interview, observation by score criterion and a questionnaire were used and some secondary data collected. Research interventions, team building, coaching, appreciative inquiry, whole brain literacy and Kolb’s experiential learning cycle were applied during the organization development intervention (ODI) phase in the Comprehensive English Class. After the traditional lecture-dominated and student-centered approach in two different groups, it was clearly indicated that interventions had a positive influence on students’ learning styles: feeling, thinking and doing styles. With regards to the four aspects of performance examined, it was easy to see that students showed higher scores in terms of sense of responsibility, self-esteem and engagement in the experimental groups after ODI. The fourth aspect, academics showed the highest level of improvement while there was no significant difference in any of the variables of the control group at the post-ODI phase.